Revisiting Teacher's Roles under Competency-Based English Teaching Curriculum: A Systematic Literature Review - Thanh, Chau Vinh; Thao, Tran Quoc (VNU Journal of Science: Education Research, 2026)
With the advancement of science and technology in the context of globalization, English education has changed to adapt to new conditions. In particular, the competency-based English teaching curriculum (CBETC) has recently been applied in many places. However, the effectiveness is not high. The reason is that the role of teachers, the primary implementers of the curriculum, has not been maximized. Therefore, this literature review aims to summarize and synthesize the characteristics of teachers’ roles in CBETC. Springer, Eric, and ScienceDirect databases and other articles by hand searching were evaluated using a comprehensive search strategy, including electronic databases, to identify relevant studies published from 2015 to 2025. The study used the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method. After analyzing the data, 37 studies were included in the review because they were relevant to the study, and data were extracted and synthesized using thematic synthesis. The findings of this study indicate that EFL teachers assume diverse roles, including controllers, assessors, managers, facilitators, fostering autonomous learning, shaping a dynamic and student-focused language learning environment, and improving self-directed learning throughout students’ language acquisition journey. This study’s findings enhance the quality of teachers’ teaching process by prioritizing students’ needs, interests, and lifelong learning.